2021
DOI: 10.1002/trc2.12152
|View full text |Cite
|
Sign up to set email alerts
|

Performance‐based IADL evaluation of older adults with cognitive impairment within a smart home: A feasibility study

Abstract: Introduction Mild cognitive impairment (MCI) is characterized by subtle deficits that functional assessment via informant‐report measures may not detect. Sensors can potentially detect deficits in everyday functioning in MCI. This study aims to establish feasibility and acceptability of using sensors in a smart home for performance‐based assessments of two instrumental activities of daily living (IADLs). Methods Thirty‐five older adults (>65 years) performed two IADL tasks in a smart home laboratory equipped w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Currently, new technologies are being explored to objectively assess IADL performance. Virtual Reality 46 and smart homes 47 seem promising methods for objective assessment of IADL performance in patients with mild cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, new technologies are being explored to objectively assess IADL performance. Virtual Reality 46 and smart homes 47 seem promising methods for objective assessment of IADL performance in patients with mild cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on older adults, the frequency of contact with grandchildren was found to be related to cognitive function ( 9 ), and contact with children or social participation was also related to depression ( 10 ). When older adults experience cognitive impairment, it becomes difficult to use devices such as telephones, and mobility also becomes difficult ( 11 ). Because the overall life satisfaction of older adults is affected by spouses, children, relatives and friends ( 12 ), if the cognitive decline worsens and contact with people around them decreases, the chances of depression may increase.…”
Section: Introductionmentioning
confidence: 99%